2006
DOI: 10.3139/217.0092
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis for Polymer Degradation in the Extrusion Process

Abstract: Polymer degradation in the extrusion process decreases quality and productivity. For this reason, it is necessary to prevent polymer degradation. In the extrusion process, polymer degradation is caused by oxidation. It depends on the processing temperature and the amount of dissolved oxygen in the molten polymer. Therefore, a quantitative analysis of these factors is required.As for the degradation characteristics of the material used in this study, temperature and oxygen concentration dependency of the oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The decrease in molecular weight could not only be assigned to the processing temperature but also to the presence of the BAG particles [18]. The mechanical properties of the scaffold were also found to decrease drastically over the short immersion time in vitro.…”
Section: Introductionmentioning
confidence: 89%
“…The decrease in molecular weight could not only be assigned to the processing temperature but also to the presence of the BAG particles [18]. The mechanical properties of the scaffold were also found to decrease drastically over the short immersion time in vitro.…”
Section: Introductionmentioning
confidence: 89%
“…The degradation makes physical properties and functional quality of a polymer worse, hence reprocessed products of high confidence are difficult to obtain. In particular, top quality is crucial in the case of thin films, for which optical and barrier properties, among other issues, play an important role [22]. These degradation processes may modify the structure and composition of the polymers and consequently change the thermal, viscoelastic and mechanical performance of the recyclates [21].…”
Section: Mechanical Recyclingmentioning
confidence: 99%
“…Therefore, for the PET/GF composites under study, the barrier melting section of the SSE is believed to increase the residence time in which glass fibers remain in contact with melted PET chains, thus maximizing the glass fiber dispersion and distribution throughout the PET. Moreover, although not measured here, some studies have shown that barrier screws are suitable for oxygen reduction in the molten polymer20 and this could help to minimize the PET degradation during extrusion, which is an additional benefit.…”
Section: Resultsmentioning
confidence: 89%